2020
DOI: 10.1101/2020.02.27.968156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome wide-association study identifies novel loci in the Primary Open-Angle African American Glaucoma Genetics (POAAGG) study

Abstract: Primary open-angle glaucoma (POAG), the leading cause of irreversible blindness worldwide, disproportionately affects African Americans. Large-scale POAG genetic studies have focused on individuals of European and Asian ancestry, limiting our understanding of disease biology. Here we report genetic analysis of the largest-ever deeply phenotyped African American population (n=5950), identifying a novel POAG-associated SNP on chromosome 11 near the TRIM66 gene (rs112369934). POAG trait association also implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 99 publications
0
25
0
Order By: Relevance
“…Recent GWAS studies demonstrated that LMX1B variants are associated with elevated IOP and POAG, even without a diagnosis of NPS or extraocular involvement, and in the absence of anterior segment abnormalities [9]. Interestingly, in our Primary Open-Angle African American Glaucoma Genetics (POAAGG) GWAS study, the variants in LMX1B were significantly associated with mean deviation (MD) baseline, but not with IOP [13]. There have been relatively few studies specifically investigating the genetic risk factors for glaucoma in African American populations, even though this population has a higher prevalence of POAG and more severe outcomes [14,15].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Recent GWAS studies demonstrated that LMX1B variants are associated with elevated IOP and POAG, even without a diagnosis of NPS or extraocular involvement, and in the absence of anterior segment abnormalities [9]. Interestingly, in our Primary Open-Angle African American Glaucoma Genetics (POAAGG) GWAS study, the variants in LMX1B were significantly associated with mean deviation (MD) baseline, but not with IOP [13]. There have been relatively few studies specifically investigating the genetic risk factors for glaucoma in African American populations, even though this population has a higher prevalence of POAG and more severe outcomes [14,15].…”
Section: Introductionmentioning
confidence: 70%
“…The genotypes of the LMX1B gene were generated by using Illumina MEGA array chip. Data generation, quality control, and single variant associations' tests were performed as described in the POAAGG GWAS [13]. In brief, the genotype calls were generated using the Genome Studio genotyping module (GT).…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] This study identified a genetic variation known as a single nucleotide polymorphism (SNP) involved in the homeostasis of the trabecular meshwork. [23] The trabecular meshwork (TM) is located in the anterior portion of the eye and regulates the outflow of the aqueous humor into circulation. [24] If resistance increases in the TM during aqueous humor outflow, intraocular pressure may rise leading to ocular hypertension.…”
Section: Genetic Influence On Ocular Hypertensionmentioning
confidence: 99%
“…The diagnosis of POAG was based on patients having an open iridocorneal angle along with characteristic glaucomatous optic nerve findings corresponding to visual field loss. Blood and saliva samples from the subjects were collected in heparinized vacutainers (BD Biosciences, San Jose, CA, USA) by venipuncture with prior written informed consent and were immediately transferred to the laboratories in ice containers for genetic analysis [32].…”
Section: Enrollment Of the Study Subjectsmentioning
confidence: 99%